RANCANGAN STRIP PLOT MODEL TETAP - Wuryandari, Triastuti; Wilandari, Yuciana; Afifah, Noor (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2008)
The experiment involve the study of the effects of two or more factors can be used the factorial designs. The factorial designs have several advantages. They are more efficient than one factor at a time experints. Furthermore, a factorial designs is necessary when interaction may be present to avoid misleading conclutions. In the Strip Plot design is factorial two factors which random factors aren’t based on main plot or the whole plot but the important is it’s interaction. There are three error in the Strip plot. They are error caused by factor A, error caused by factor B and error by A and B interaction. Keywords: Factorial, Strip Plot, Interaction